Characterization of damage and triboparticles resulting from fretting of Incoloy 800 steam generator tubes against different materials - Soria, Sergio Raul (2017)
Fretting experiments of Incoloy 800 steam generator tubes against AISI 304, AISI 1060 and Cu (99.9%) cylindrical pads were carried out to evaluate the influence of pad composition on wear damage and on the nature of the triboparticles originated in the process. Tests were performed up to 106 cycles in air under an imposed relative displacement amplitude of 75 ± 5 µm and a normal contact load of 40 ± 5 N. Surface damage was characterized using light microscopy, scanning electron microscopy and optical profilometry. The triboparticles detached during the tests were analyzed by transmission electron microscopy and energy dispersive X-ray spectroscopy. Debris particles were agglomerates of nano-crystalline oxide grains sized between 5 nm and 20 nm of the following phases: NiO, (Fe,Cr)2O3 and (Ni,Fe)(Fe,Cr)2O4 in the case of the AISI 304 pad, (Cu,Ni)(Fe, Cr)2O for the Cu pad and (Fe,Cr)2O3 in the case of the AISI 1060 pad. A preponderance of adhesive wear was found for the Cu and AISI 1060 pads while abrasive wear was predominant in the case of the AISI 304 pad. Tube-pad differential hardness was found to have a minor influence on wear rate compared to the acting main wear mechanism.